Angiogenic factors combined with clinical risk factors to predict preterm pre‐eclampsia in nulliparous women: a predictive test accuracy study. Issue 10 (21st March 2013) - Myers, JE; Kenny, LC; McCowan, LME; Chan, EHY; Dekker, GA; Poston, L; Simpson, NAB; North, RA; ,
Abstract : Objectives: To assess the performance of clinical risk factors, uterine artery Doppler and angiogenic markers to predict preterm pre‐eclampsia in nulliparous women. Design: Predictive test accuracy study. Setting: Prospective multicentre cohort study Screening for Pregnancy Endpoints (SCOPE). Methods: Low‐risk nulliparous women with a singleton pregnancy were recruited. Clinical risk factor data were obtained and plasma placental growth factor (PlGF), soluble endoglin and soluble fms‐like tyrosine kinase‐1 (sFlt‐1) were measured at 14–16 weeks of gestation. Prediction models were developed using multivariable stepwise logistic regression. Main outcome measure: Preterm pre‐eclampsia (delivered before 37 +0 weeks of gestation). Results: Of the 3529 women recruited, 187 (5.3%) developed pre‐eclampsia of whom 47 (1.3%) delivered preterm. Controls ( n = 188) were randomly selected from women without preterm pre‐eclampsia and included women who developed other pregnancy complications. An area under a receiver operating characteristic curve (AUC) of 0.76 (95% CI 0.67–0.84) was observed using previously reported clinical risk variables. The AUC improved following the addition of PlGF measured at 14–16 weeks (0.84; 95% CI 0.77–0.91), but no further improvement was observed with the addition of uterine artery Doppler or the other angiogenic markers. A sensitivity of 45% (95% CI 0.31–0.59) (5% false‐positive rate) and post‐test probability of 11% (95% CI 9–13) were observed using clinical risk variables and PlGF measurement. Conclusions: Addition of plasma PlGF at 14–16 weeks of gestation to clinical risk assessment improved the identification of nulliparous women at increased risk of developing preterm pre‐eclampsia, but the performance is not sufficient to warrant introduction as a clinical screening test. These findings are marker dependent, not assay dependent; additional markers are needed to achieve clinical utility.